Effects of the didactic model of game action competences on tactical performance, motivation, and perception of skill in young football players (2021)
ABSTRACT: Purpose: This study compares the learning effects of the Didactic Model Game Action Competences (DMGAC) with the Didactical Model of Direct Instruction (DMDI) in tactical performance, motivation, and perception of skill in young football players. DMGAC is a new didactic model that is based on constructivism educational theory. It promotes the learning of tactical behaviors, decision making, autonomy, and cognitive development. This new model is intended to be used in extracurricular settings such as sport clubs with competitive purposes.Method: A randomized control trial was performed in parallel. The participants were 36 children (U11 yrs.), who practiced football regularly in an extracurricular sport program. Both didactic models were implemented to teach the fundamental principles of football during 12 sessions of 80 min and evaluated in three stages (i.e., pretest, post-test, and retention test). The experimental group implemented DMGAC with five didactic strategies (i.e., smallside games, psychokinetic games, 1 on 1 situations, self-directed learning of technical skills, and global game or representation). The control group used DMDI with three didactic strategies (i.e., technical skills, simulated game situations, and global game). Tactical performance index, motivation, and perception of skill were measured with the System of Tactical Evaluation in Football, Sport Motivation Scale, and Tactical Skills Inventory Sports, respectively. Results: The obtained outcomes suggest that the fundamental football principles were learned more effectively through a constructivism-based model (DMGAC) (p = 0.020). The tasks proposed in this model promote the integral development of game competences and autonomy; in addition, there was a significant tendency towards intrinsic motivation and a tendency towards a greater perception of tactical ability.Conclusion: Based on these findings, the children who participated in a teaching program through DMGAC attained a higher tactical performance index than those who participated in a teaching program through DMDI.